Services and the new economic landscape - William B. Beyers; David P. Lindahl (European Regional Science Association (ERSA), 1998)
The growth of the service economy in advanced and developing economies has created what are now being referred to as New Economic Landscapes. These landscapes are not only built forms, they are job generators and new sources of economic power for the regions that house them. This service economy is variegated, with differing sources of demand, and varying geographies of supply. A dynamic element in this mileaux is the evolving producer service complex–an amalgum of financial, business, legal, and professional services, which have had rapid expansion in most parts of the global economy. Existing conceptual paradigms in regional science have not fully acknowledged the manifold importances of The New Economic Landscape–they have essentially danced around it. In this paper we zero in on the central role of services, as well as primary and secondary industries, in the current economic era, relating on the one hand the expansion of information-oriented producer services to patterns of evolution in goods producing primary and secondary industries, as well as placing these dynamic producer service sectors in context of the ongoing expansion of the larger service sector. The goal of this paper is to make clear the regional development implications of the complex processes of service industry development occuring globally, while simultaneously speaking to the implications of this transformation for regions and theory in regional science. In this regard we build on recent conceptualizations of the role of industrial and information networks, economic underpinnings of regional economies, new perspectives on entrepreneurial activity, and behaviors which we have documented are important to the success of service industries on the New Economic Landscape. In doing so, we take advantage of and extend conceptualizations which have been developed largely in management science as they bear on firm-level performance, and marry these ideas with the emerging literature on the importance of the vital position of regions in the so-called global economy.
Keywords: 330